Comparative evaluation of intranasal dexmedetomidine, intranasal midazolam, and nitrous oxide for conscious sedation of anxious children undergoing dental treatment: A randomized cross-over trial - Palak Janiani; Deepa Gurunathan; Ramsesh Manohar (Wolters Kluwer Medknow Publications, 2024)
Background: Pharmacological methods, specifically sedatives, have gained popularity in managing the behavior of children during dental appointments. Aim: The aim of this study was to compare 1 m/kg intranasal dexmedetomidine, 0.3 mg/kg intranasal midazolam, and nitrous oxide in evaluating the level of sedation, behavior of the child, onset of sedation, physiologic signs, and adverse effects. Materials and Methods In this cross-over trial, 15 children aged 6-8 years were randomized to receive intranasal atomized dexmedetomidine, intranasal atomized midazolam, and inhalation nitrous oxide at three separate visits. After administering the sedative agent, a single pulpectomy was performed during each appointment, and the outcomes were recorded. The washout period between each visit was 1 week. Results: All three sedative agents were equally effective in controlling overall behavior. Dexmedetomidine showed lower sedation level scores (agitated; score 9) than the other groups. There was a statistically significant difference in the onset of sedation, with dexmedetomidine having the longest onset of 36.2 ± 9.47 min. Coughing and sneezing were predominantly observed after administration of intranasal midazolam. Oxygen saturation levels were statistically lower in the intranasal midazolam group during local anesthesia administration and post-treatment. Conclusion: 0.3 mg/kg intranasal midazolam is as effective as nitrous oxide sedation for controlling behavior and providing adequate sedation in pediatric dental patients. However, 1 m/kg dexmedetomidine did not provide the same level of sedation and had a significantly longer onset. 0.3 mg/kg intranasal midazolam is an effective alternative to nitrous oxide sedation in anxious children.